2014
DOI: 10.1111/jog.12452
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of amniotic fluid embolism: An experience of 29 years

Abstract: AFE patients were classified into two types based on presenting signs and symptoms. Knowledge of the various initial symptoms of AFE enables a correct diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In case 2, the timing of treatment appeared to be appropriate, and therefore, this patient required a minimum amount of blood transfusion. It has been reported that hysterectomy should be considered early before the complete development of coagulopathy . Removal of the uterus, which is the location of the anaphylactic reaction in DIC‐type AFE, might improve coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In case 2, the timing of treatment appeared to be appropriate, and therefore, this patient required a minimum amount of blood transfusion. It has been reported that hysterectomy should be considered early before the complete development of coagulopathy . Removal of the uterus, which is the location of the anaphylactic reaction in DIC‐type AFE, might improve coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Initial incoagulable bleeding in all cases resembled the initial symptom of uterine atony. 9 However, DIC-type AFE advances DIC predominantly in PPH because of the rapid consumption of coagulation factors. In cases of uterine atony, massive atonic bleeding results in consumption of coagulation factors, following DIC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Components of amniotic fluid can be determined with hematoxylin-and-eosin, alcian-phloxine-martius yellow (testing for mucin), cytokeratin AE1/AE3 (for squamous cells), ZnCp-1 (for meconium), and C5aR stain (for complement activation) [34][35][36]. It has been noted, however, that only about 50% of patients with AFE had detectable fetal debris present in maternal circulation [6,37].…”
Section: Diagnostic Considerationsmentioning
confidence: 98%
“…Substantial redevelopment would be required if it were to be used in diabetes. Amniotic fluid embolism (AFE) is a rare and often undiagnosed cause of acute pulmonary hypertension in pregnancy and uncontrollable postpartum uterine hemorrhage, precipitated by an ingression of amniotic fluid into maternal blood [13,14]. While decreased levels of complement components C3 and C4 have been reported in AFE patients who subsequently develop disseminated intravascular coagulation, an involvement of C1 in AFE had not been described.…”
mentioning
confidence: 99%